THE EFFECT OF A COMBINATION OF DEEP BREATHING TECHNIQUES AND POSITIVE SELF-TALK THERAPY ON ANXIETY IN HYPERTENSIVE PATIENTS - Aulya Nurazizah; Iwan Somantri; Ridwan Kustiawan; Peni Cahyati; Ristrini Ristrini (Jurnal Kesehatan Kusuma Husada, 2026)
Background: Hypertension is a major global health issue that frequently triggers psychological distress, such as anxiety, which can further destabilize blood pressure. Deep breathing techniques promote physiological relaxation by activating the parasympathetic nervous system, whereas positive self-talk therapy helps reduce anxiety by modifying negative thoughts into more adaptive and positive ones. As these interventions target complementary physiological and psychological mechanisms, their combination is expected to provide a more comprehensive effect in reducing anxiety among patients with hypertension. This study aims to determine the effect of combining deep breathing techniques and positive self-talk therapy on anxiety scores among hypertensive patients within the Kersanegara Community Health Center working area, Tasikmalaya City.Methods: This quantitative study employed a quasi-experimental approach with a pretest-posttest control group design. A total of 42 respondents were selected via purposive sampling and divided equally into an intervention group (n = 21) and a control group (n = 21). The intervention group received the combined therapy for 5 days (15–20 minutes per session), while the control group received standard care and health education. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) and analyzed using dependent and independent t-tests.Results: The average anxiety score in the intervention group significantly decreased from 22.05 to 13.71 (p = 0.000). Meanwhile, the control group showed no significant reduction, changing from 21.05 to 20.29 (p = 0.217). The post-intervention independent t-test confirmed a significant difference in anxiety levels between the two groups (p = 0.000).Conclusion: The combination of deep breathing techniques and positive self-talk therapy is highly effective in reducing anxiety among hypertensive patients and can serve as an alternative non-pharmacological nursing intervention. This intervention may be incorporated into routine nursing care and community-based hypertension management programs, particularly in primary healthcare settings, to help nurses manage anxiety among hypertensive patients.